Stress distribution in fixed mandibular prostheses fabricated by CAD/CAM and conventional techniques: Photoelastic and strain gauge analyses - de Medeiros, Rodrigo-Antonio (2019)
The aim of this study was to evaluate the distribution of stress in complete fixed mandibular prostheses with infrastructures (IE) fabricated with different materials and techniques, under compressive force. A model of an edentulous mandible, which received five 4x11 mm external hexagon implants between the mental foramens, was fabricated. The groups were divided into: Group I - IE in nickel-chromium with an acrylic resin occlusal coating; Group II - IE in nickel-chromium with a ceramic occlusal coating; Group III - IE milled in zirconia with a ceramic coating. For the photoelastic methodology, 70 N axial loads were applied in three regions. Photographic images were taken and analyzed according to the number of high-intensity fringes. For the strain gauge methodology, the measurement of stresses was performed in two distinct regions. The same compression tests described earlier were then performed. The registered stress values were grouped in tables and submitted to two-factor variance analysis (ANOVA) and the Tukey test with 5% significance. The results of the two methodologies demonstrated smaller stress values for Group I, when compared to the other groups. It was possible to conclude that the complete fixed prostheses, with infrastructures cast in metal and acrylic occlusal coating, demonstrated better biomechanical results.